Interactive effects of solar radiation and dissolved organic matter on bacterial activity and community structure - Pérez, María Teresa (Blackwell Publishing Ltd, 2007)
We studied the interactive effects of dissolved organic matter (DOM) and solar radiation on the activity and community structure of bacteria from an alpine lake. Activity was assessed both at the community level as leucine incorporation rates and at the single-cell level by microautoradiography. Fluorescent in situ hybridization and signal amplification by catalysed reporter deposition (CARD-FISH) was used to track changes in the bacterial community composition. Bacteria-free filtrates of different DOM sources (lake, algae or soil) were incubated either in the dark or exposed to solar radiation. Afterwards, the natural bacterial assemblage was inoculated and the cultures incubated in the dark for 24–48 h. Bacterial activity was enhanced in the first 24 h in the soil and algal DOM amendments kept in the dark. After 48 h, the enhancement effect was greatly reduced. The initial bacterial community was dominated by Betaproteobacteria followed by Actinobacteria. The relative abundance (expressed as a percentage of DAPI-stained cells) of Betaproteobacteria increased first in dark incubated DOM amendments, but after 48 h no significant differences were detected among treatments. In contrast, the relative abundance of Actinobacteria increased in pre-irradiated DOM treatments. Although Betaproteobacteria dominated at the end of the experiment, the relative abundance of their R-BT subgroup differed among treatments. Changes in bacterial community activity were significantly correlated with those of the relative abundance and activity of Betaproteobacteria, whereas the contribution of Actinobacteria to the bulk activity was very modest. Our results indicate a negative effect of DOM photoalteration on the bulk bacterial activity. The magnitude of this effect was time-dependent and related to rapid changes in the bacterial assemblage composition.